A Tool for Healthcare Information Integration - Palaniappan, Sellappan; Ng, Yih Huey (Universiti Utara Malaysia Press, 2006)
Currently, information collected by the various healthcare providers (hospitals and clinics) in Malaysia is not integrated. Each collects information for its own internal use. The information is not aggregated and analyzed at the state or national level to provide useful information for decision making (e.g., by the Ministry of Health). Extracting and aggregating information from diverse data sources (databases) has always been a challenge for the healthcare industry. This paper presents a tool for integrating healthcare information from several relational databases into a single data warehouse. It is simple, cost-effective and yet solves the information integration problem. It consists of a schema mapping process which is partially automated and an Extraction, Transformation and Loading (ETL) process which is fully automated. To demonstrate its viability, a data warehouse containing materialized data is built from three databases, namely, Access, SQL Server and Oracle. It is implemented using the Microsoft .NET Framework.